Securitization, Credit Rating and Issuers’ Characteristics - Mauricio Palmada Fernandes; Hsia Hua Sheng; Mayra Ivanoff Lora (BBR: Brazilian Business Review)
Given the growth of securitization through Credit Receivables Investment Funds (Fundos de Investimento em Direitos Creditórios - FIDCs) in Brazil in recent years, this work aims to investigate empirically the relationship between securitization and credit rating in the Brazilian market. All issues of FIDCs held by banks and registered in the CVM from 2005 to July 2010 were analyzed. The two hypotheses discussed by Gorton and Souleles (2005) were confirmed to Brazilian financial institutions. There is evidence of an implied contract between the transferor companies and investors in securitizations made via FIDCs. Companies with higher credit risk, worst ratings, tend to securitize more. However no relationship was found between securitization and asset value, amount of loans or capital ratio.